Influence of test distance on change of direction speed test results - Sayers, M. G. L. (The Journal of Strength and Conditioning Research, 2015)
This study assessed the relationships between linear running velocity and change of direction (CoD) ability and how assessing CoD ability over distances =5 m influences test reliability. Participants (n = 15) from amateur rugby league teams performed 3 trials of a 20-m sprint test (light gates at 5, 10, and 20 m) and 6 trials of the 5-0-5 agility test. Twelve participants repeated the 5-0-5 test several weeks later. A three-dimensional motion capture system (250 Hz) was used to track the center of mass at 0.3, 0.5, and 1.0 m either side of the turn and identify specific CoD phase times. Pearson's correlations showed strong significant relationships between the 5-0-5 time and 5-m (r = 0.89, p < 0.001), 10-m (r = 0.91, p < 0.001), and 20-m sprint times (r = 0.93, p < 0.001). However, the strength of these relationships decreased (r < 0.65, p > 0.05) when CoD ability was measured over distances less than 0.5 m. Analysis of coefficient of variation (CV%) data indicated that the 5-0-5 test had high intratest (CV% = 2.8) and intertest reliability (CV% = 1.3), with these data decreasing for distances less than 1 m (CV% = 3.5-6.9). Specific movement phase times were the least reliable measures of CoD ability (CV% = 4.7-53.6). Results suggest a bias between high-speed linear running ability and 5-0-5 time. However, an effective compromise can be found between test reliability and the external validity by assessing CoD ability over 1 m. Findings indicate that the current practice of assessing CoD ability over large distances in questionable.